The X-Efficiency of Shariah and Conventional Banking’s in Indonesia - Aimatul Yumna (Universitas Prasetiya Mulya, 2020)
This paper investigates the X-efficiency of fifteen commercial banks in Indonesia consisting of seven syariah banks and eight conventional banks. This study uses three stages of data analysis: non-parametric data envelopment analysis (DEA) approach, t-test, and multiple regression method. The results show that in the period of this study, both syariah and conventional banks in Indonesia have not reached the optimal level of efficiency. However, conventional banks obtain a higher level of allocative and total efficiency compared to syariah banks. The inefficiency of Islamic banks is stemed from allocative inefficiency rather than technical problems. The bank’s X-efficiency is significantly influenced by size, rather than number of banking channels and staff costs. This study provides important implications for syariah banking in order to improve X- efficiency and compete in the banking industry in Indonesia by focusing on the improvement of the combination of quality assets.Keywords: X-efficiency, DEA, Shariah and conventional banks* Universitas Negeri Padang, Jl. Prof. Dr. Hamka, Air Tawar Bar., Kec. Padang Utara, Kota Padang, Sumatera Barat 25171 https://doi.org/10.21632/irjbs.13.2.149-159